Training and Assistance for the Mada Mbuha Tourism Awareness Group (POKDARWIS) in Palama Village to Improve the Creative Economy and Village Income - hardyanti, hardyanti; Fauzi, Azra; Islamiah, Muarif (Abdi Masyarakat, 2024)
Community-based tourism development in Palama Village, particularly in Doro Leme Valley, holds significant potential for enhancing community welfare through participative and sustainable management. This article discusses the implementation of an empowerment program for the Mada Mbuha Tourism Awareness Group (Pokdarwis) using the Participatory Rural Appraisal (PRA) approach, which involves training in tourism management, digital marketing strategies, and technology application in tourism promotion. Through PRA, the community actively participates in planning through evaluation, allowing a more adaptive approach to local needs. The program results indicate an increase in the Pokdarwis members' capacity to manage village tourism, optimize technology for promotion, and develop culture-based tourism packages, contributing to the attraction of tourism. However, infrastructure limitations and funding constraints remain challenges for program sustainability. Collaboration with the government and private sector is required to support better infrastructure and accessibility. With a holistic approach, the tourism potential of Palama Village can be realized sustainably, providing positive impacts on the local economy as well as on cultural and environmental preservation.